Root coverage employing an envelope technique or guided tissue regeneration with a bioabsorbable membrane - Müller, Hans-Peter; Stahl, Marianne; Eger, Thomas (Journal of periodontology, 1999)
Different treatment modalities have been described for root coverage in cases of gingival recession. The aim of the present study was to evaluate the postsurgical outcome of 2 modes of surgical root coverage of predominantly shallow, Class I or II, gingival recessions.
Gesehen am 12.03.2021